GAMBARAN UPAYA PENCEGAHAN LOW BACK PAIN PADA PERAWAT DI RSUD SELASIH PANGKALAN KERINCI - Silalahi, Novitasari Wijayanti; Erwin, Erwin; Utami, Gamya Tri (Coping: Community of Publishing in Nursing; Vol 10 No 5 (2022): Oktober 2022DO - 10.24843/coping.2022.v10.i05.p09, 2022)
Low back pain is an uncomfortable condition on the lower back that comes with limitation of activity and pain when moving or mobilizing. One of the occupations with a high risk of suffering low back pain is nurse. This is related to ergonomic activities of nurse in hospitals. This study aims to describe the efforts of low back pain prevention in nurses. This study uses descriptive quantitative design and was conducted in Selasih Hospital, Pangkalan Kerinci. The sample of the study involves 53 respondents of nurses and uses stratified random sampling technique. Analysis in this study uses univariate analysis. The instrument in the study is a questionnaire based on back injury prevention by Kansas State University Research and Extension. The result shows that in the application of safe patient handling, assistive devices utilization, and stretching exercises, majority of the respondents often apply with percentages in consecutive are 58,5%, 67,9%, and 66,0%. The result also shows in the application of correct standing posture, correct sitting posture, and correct sleeping posture, majority of the respondents often apply with percentages in consecutive are 56,6%, 67,9%, and 54,7%. It could be concluded that efforts to prevent low back pain in nurses are often applied.